Evaluation of California's Alcohol and Drug Screening and Brief Intervention Project for Emergency Department Patients - Susan I Woodruff (Western Journal of Emergency Medicine, 2013)
Introduction: Visits to settings such as emergency departments (EDs) may present a “teachable moment” in that a patient may be more open to feedback and suggestions regarding their risky alcohol and illicit drug-use behaviors. Screening, Brief Intervention, and Referral to Treatment (SBIRT) is an ’opportunistic’ public health approach that targets low-risk users, in addition to those already dependent on alcohol and/or drugs. SBIRT programs provide patients with comprehensive screening and assessments, and deliver interventions of appropriate intensity to reduce risks related to alcohol and drug use. Methods: This study used a single group pre-post test design to assess the effect of the California SBIRT service program (i.e., CASBIRT) on 6 substance-use outcomes (past-month prevalence and number of days of binge drinking, illegal drug use, and marijuana use). Trained bilingual/bicultural Health Educators attempted to screen all adult patients in 12 EDs/trauma centers (regardless of the reason for the patient’s visit) using a short instrument, and then delivered a brief motivational intervention matched to the patient’s risk level. A total of 2,436 randomly selected patients who screened positive for alcohol and/or drug use consented to be in a 6-month telephone follow-up interview. Because of the high loss to follow-up rate, we used an intention-to-treat approach for the data analysis. Results: Results of generalized linear mixed models showed modest reductions in all 6 drug- and alcohol-use outcomes. Men (versus women), those at relatively higher risk status (versus lower risk), and those with only one substance of misuse (versus both alcohol and illicit drug misuse) tended to show more positive change. Conclusion: These results suggest that SBIRT services provided in acute care settings are associated with modest changes in self-reported recent alcohol and illicit drug use. [West J Emerg Med. 2013;14(3):263–270.]